2021
DOI: 10.1007/s00414-021-02526-x
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord injury as an indicator of abuse in forensic assessment of abusive head trauma (AHT)

Abstract: Abusive head trauma (AHT) in children is notoriously one of the most challenging diagnoses for the forensic pathologist. The pathological “triad”, a combination of intracranial subdural haematoma, cerebral oedema with hypoxic-ischaemic changes and retinal haemorrhages, is frequently argued to be insufficient to support a corroborated verdict of abuse. Data from all available English-language scientific literature involving radiological and neuropathological spinal cord examination is reviewed here in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 70 publications
1
19
0
Order By: Relevance
“…Along the same lines, ENPP2 displays the highest CNS expression in the corpus callosum, spinal cord and pigmented layer of the retina [60]. As mentioned above and in line with data in the HPA, F5 is dominantly expressed in the corpus callosum, the pons, and the medulla oblongata, brain regions proximate to the spinal cord, and which frequently report injuries in AHT but not in accidental head trauma in infants [2, 58, 59].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Along the same lines, ENPP2 displays the highest CNS expression in the corpus callosum, spinal cord and pigmented layer of the retina [60]. As mentioned above and in line with data in the HPA, F5 is dominantly expressed in the corpus callosum, the pons, and the medulla oblongata, brain regions proximate to the spinal cord, and which frequently report injuries in AHT but not in accidental head trauma in infants [2, 58, 59].…”
Section: Discussionmentioning
confidence: 77%
“…We observed that the several proteins upregulated in the serum of AHT cases (i.e., ENPP2, BASP1, LCAT) including the highly elevated F5 protein display an overlap of their CNS expression with the anatomical lesions found in the brain of infant victims of AHT, but not accidental head trauma [58, 59].…”
Section: Discussionmentioning
confidence: 99%
“…Upper cervical spinal cord injury is another important non-negligible factor that increases the severity of AHT [ 8 , 9 , 25 ]. To elucidate why CPA occurs, it is necessary to consider the possibility of upper spinal cord injury.…”
Section: Why Does Aht Cause Cpa?mentioning
confidence: 99%
“…Colombari et al [1] present a literature review to assess the contribution of spinal cord changes in differentiating abusive from accidental head trauma. This premise itself defies logic.…”
Section: Sirmentioning
confidence: 99%